Spatial distribution of FMISO in head and neck squamous cell carcinomas during radio-chemotherapy and its correlation to pattern of failure. (21st October 2015) - Zschaeck, Sebastian; Haase, Robert; Abolmaali, Nasreddin; Perrin, Rosalind; Stützer, Kristin; Appold, Steffen; Steinbach, Jörg; Kotzerke, Jörg; Zips, Daniel; Richter, Christian; Gudziol, Volker; Krause, Mechthild; et al.
ABSTRACT: Background. Tumour hypoxia can be measured by FMISO-PET and negatively impacts local tumour control in patients with head and neck squamous cell carcinoma (HNSCC) undergoing radiotherapy. The aim of this post hoc analysis of a prospective clinical trial was to investigate the spatial variability of FMISO hypoxic subvolumes during radio-chemotherapy and the co-localisation of these volumes with later recurrences as a basis for individualised dose prescription trials with dose escalation defined by FMISO-PET. Methods. Sequential FMISO scans of 12 (of 25) patients presenting residual hypoxia taken before (FMISOpre) and during (FMISOw1–FMISOw5) radio-chemotherapy were analysed regarding the stability of the FMISO subvolumes and, in case of local failure, their correlation to local relapse. Results. Consecutive FMISO-PET positive volumes could be classified as moderately stable with Dice conformity indices of 62% and 58% up to the second week of treatment. Substantial volumetric variation during treatment was observed, with more than 20% geographic miss in all patients and more than 40% in half of the patients. The localisation of the maximum standardised uptake value (SUVmax ) differed with a mean distance of 7.0 mm and 13.5 mm between the pre-therapeutic and first or second FMISO-PET during treatment. A stable hypoxic consensual volume (i.e. overlap of pre-therapeutic FMISO and intra-treatment FMISO subvolumes up to week two, generated by different contouring methods) was determined for six patients with imaging information of local recurrence. Three of these six local recurrences were located within this consensual volume. Conclusions. Our data suggest that selective dose painting to hypoxic tumour subvolumes requires adaptation during treatment and sufficient margins. An alternative strategy is to escalate the dose to the gross tumour volume, accepting lesser escalation of dose outside hypoxic areas if indicated by constraints for organs at risk.